An implementation of the 2-point block arithmetic mean iterative method for first kind linear fredholm integral equations - Mohana Sundaram Muthuvalu; Jumat Sulaiman (World Academic Press, World Academic Union, England, UK, 2012)
In recent decades, many researches involving Arithmetic Mean (AM) iterative methods for solving matrix equations that arise from various scientific problems have been conducted. In this paper, application of the 2-Point Block Arithmetic Mean (2-BLAM) method to solve first kind linear Fredholm integral equations with semi-smooth kernel is investigated. The formulation and implementation of the method are discussed. Furthermore, numerical results of the method on test problems are also included.